Synergetic effects of waste engine oil and crumb tyre rubber on bitumen modification - Muhammad Fahad Ali; Rizwan Ali Memon; Ali Raza Lashari; Muhammad Hamza Siddiqui; Aisha Ahmed (Penerbit Universiti Kebangsaan Malaysia, 2023)
Bitumen is a widely used road infrastructure material exhibiting black color and sticky consistency and is known for its versatile use and thermoplastic nature. In recent years, predicting road life has been arduous due to increasing traffic, global warming, and ever-changing stresses on pavements. Meanwhile, a large amount of waste engine oil (WEO) and vehicle tyres from various automobiles is disposed of into the atmosphere as hazardous waste. Relatedly, heavy metals and the huge capital involved in the sustainable treatment of these materials have been challenging. Therefore, this study aims to analyze modified bitumen using (WEO) in combination with waste crumb tyre rubber (CTR), thus reducing virgin bitumen (VB) use and making bitumen a sustainable material. During the characterization of modified bitumen, the following WEO concentrations were utilized: 3%, 5%, 7%, and 9%, and the following CTR concentrations: 5%, 7%, 9%, 12%, and 15%. The properties of modified and virgin bitumen were compared. It has been found that the blend of 5% CTR and 9% WEO exhibit the highest penetration value and the lowest softening temperature of all the samples examined. As a result, this mixture can be used to reduce the excessive brittleness of bitumen to a greater extent. Moreover, the flash and fire point values have increased after modification, while the ductility and specific gravity values have decreased. In summary, the modified bitumen has shown promising results regarding physical changes in bitumen.